Supplementation of Vitamin D in the Postdelivery Period of Women with Previous Gestational Diabetes Mellitus: Systematic Review and Meta-Analysis of Randomized Trials - Meline Rossetto Kron-Rodrigues; Marilza Vieira Cunha Rudge; Silvana Andrea Molina Lima (Revista Brasileira de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate the effects of vitamin D supplementation in the postpartum period of women with previous gestational diabetes mellitus (GDM). Methods Randomized clinical trials of pregnant women with GDM of any chronological, gestational age and parity, with no history of previous disease who received vitamin D supplementation in the prenatal and/or postpartum period and were evaluated in the postpartum period were included. The PubMed, EMBASE, Cochrane, and LILACS databases were consulted until July 2019. Serum vitamin D concentration (25- hydroxyvitamin D in nmol/L), fasting blood glucose, glycated hemoglobin, serum calcium concentration, homeostatic model assessment of insulin resistance (HOMAIR), quantitative insulin sensitivity check index (QUICKI), parathyroid hormone (PTH) and body mass index (BMI) were evaluated. Similar results in at least two trials were plotted using the RevMan 5; Cochrane Collaboration, Oxford, Reino Unido. The quality of the evidence was generated according to the classification, development, and evaluation of the classification of the recommendations. Results Four studies were included in the present review (200 women). The findings indicate that there is no difference in the postpartum period in women diagnosed with previous GDM who received vitamin D supplementation in the prenatal and/or in the postpartum period, showing only that there was a significant increase in the concentration of vitamin D (relative risk [RR]: 1.85; 95% confidence interval [CI]: 1.02-2.68). Conclusion This increase in the concentration of vitamin D should be interpreted with caution, since the assessment of the quality of the evidence was very low. For the other analyzed outcomes, there was no significance between the intervention and control groups, and the outcomes, when analyzed in their strength of evidence, were considered very low and low in their evaluation.